CITRAL AMELIORATES ISCHEMIC BRAIN DAMAGE IN STREPTOZOTOCIN INDUCED DIABETES IN RATS THROUGH AUTOPHAGY ACTIVATION - Tripathi, Dinesh; Tiwari, Sunita; Mishra, Chetna; Bhaflacharya, Sandeep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Focal cerebral ischemia is one of the leading causes of death and disability worldwide, and more than 30% of stroke patients are known to be diabetic. Accumulating evidence indicates that autophagy can contribute to cell death processes under pathological conditions. Citral, a monoterpene found in the essential oil of several plants, such as Cymbopogon citratus, has been reported to have antioxidant and anti-inflammatory activity. The aim of this study was to examine the neuroprotective effects of citral against ischemic stroke in diabetic rats and co-relate its probable effects on autophagy. METHODOLOGY Streptozotocin (STZ) stimulation-induced diabetic rats were subjected to 1 h ischemia followed by reperfusion. The diabetic rats received different dosages of citral vehicle at baseline and 24 h after the middle cerebral artery occlusion (MCAO). Neurological deficit, lipid profile, blood glucose, and molecular biological tests (expression of PI3K/AKT/ mTOR pathway-related proteins) were then performed to demonstrate the neuroprotective effects and mechanism in I/R injured diabetic rat. RESULT The results showed that citral markedly attenuated IL-1β, IL-6, and TNF-α levels. Meanwhile, treatment with citral retained serum GSH levels, led to a lower MDA level and also ameliorated neurologic outcome in rats. Citral treatment significantly decreased serum glucose level, serum TG, TC and LDL. Citral administration dramatically upregulated the expression of p62, and downregulated the level of LC3, beclin-1. CONCLUSION All data reveal that citral could effectively ameliorate cerebral ischemia/reperfusion injury via ameliorating inflammatory response, oxidative stress, and improving autophagy through PI3K/Akt/mTOR signaling pathway in diabetic rats.